2013
DOI: 10.4103/0971-9261.107013
|View full text |Cite
|
Sign up to set email alerts
|

Multiple venous aneurysms of neck

Abstract: Venous aneurysm of neck is a rare anomaly, usually presenting as a painless mass which increases in size on valsalva maneuver. A child with multiple aneurysms of the right common facial and external jugular veins diagnosed on Doppler ultrasonography and magnetic resonance venography is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…With regard to management, because IJ aneurysms are considered to be self-limiting, operative intervention is usually reserved for cosmetic or symptomatic reasons[ 2 , 5 , 10 , 18 ]. Although extremely rare, if there is significant concern for thrombosis, embolization or impending rupture, resection is justified[ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With regard to management, because IJ aneurysms are considered to be self-limiting, operative intervention is usually reserved for cosmetic or symptomatic reasons[ 2 , 5 , 10 , 18 ]. Although extremely rare, if there is significant concern for thrombosis, embolization or impending rupture, resection is justified[ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…With regard to management, because IJ aneurysms are considered to be self-limiting, operative intervention is usually reserved for cosmetic or symptomatic reasons[ 2 , 5 , 10 , 18 ]. Although extremely rare, if there is significant concern for thrombosis, embolization or impending rupture, resection is justified[ 10 ]. Various approaches have been described which have been largely based on size and location, including anterior SCM, transverse cervical and median sternotomy incisions[ 4 , 5 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histopathological changes in those cases treated with surgical resection include a thinning of the muscular and elastic layers; however, the great majority of cases showed no significant changes compared with the normal venous wall. [17,92] Several authors have found this abnormality in patients with neurofibromatosis type 1 and in Ehlers–Danlos syndrome. [18,39,49,67] In the present review, there was no significant association with these pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…Venous aneurisms of the neck are rare entities, typically asymptomatic, potentially complicated by thrombosis or rupture ( 1 , 2 ). Venous malformations of the neck associated with thromboembolic events are rarely reported in the available literature ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%